Secondary Folds Contribute Significantly to the Total Surface Area in the Olfactory Organ of Chondrichthyes - Ferrando, Sara; Amaroli, Andrea; Gallus, Lorenzo; Aicardi, Stefano; Di Blasi, Davide; Christiansen, Jørgen S.; Vacchi, Marino; Ghigliotti, Laura (Frontiers in Physiology, 2019)
The olfactory organ of Chondrichthyes is characterized by a central support with several lamellae covered by a sensory olfactory epithelium. Although secondary folds are present on the lamellae in all the chondrichthyan species analyzed to date, their shape and size have not been described. We here analyze the olfactory organ of 13 elasmobranch and 1 holocephalan species, describe the shape of the secondary folds and evaluate how they contribute to the actual epithelial surface area. The secondary folds vary in shape and size, and they should always be considered when comparing the epithelial surface area among species. Because of the complexity of the shapes, we approach the description of the secondary folds by analyzing histological sections of the olfactory lamellae to obtain representative silhouettes. We introduce two indexes in order to describe a 2D-sectioned shape of the secondary folds. Considering the different numerical parameters which describe the morphology of the olfactory organ (secondary folds included), a principal component analysis elucidates the possible e ecological role and phylogenetic relationship of the chondrichthyan olfactory organ.